(untitled) - Browning, Edgar K. Browning (New York, 2004)
Written by distinguished authorities in the field, this book presents a practical, real-world approach to microeconomics through a wealth of applications that demonstrate the relevance of microeconomics to everyday life
Keywords: Microeconomics,Microeconomics